Further notes on the reproduction of Hydrops caesurus (Serpentes: Colubridae) from Corrientes, Argentina - Etchepare, Eduardo Gabriel (2012)
Hydrops caesurus Scrocchi, Ferreira, Giraudo, Ávila and Motte 2005 is a mainly aquatic xenodontinae occurring in areas of the Paraná and Plata River basins, from Pantanal in Mato Grosso do Sul, Brazil, through Paraguay and Paraná rivers (Scrocchi et al., 2005). In Argentina, the species is only known from two localities: Bella Vista and San Miguel, both in the Corrientes province (Williams and Couturier, 1984; Álvarez et al., 2003). Its natural history is poorly known. The only information is referred to one clutch of nine eggs found on the bank of Carambola stream (Álvarez et al., 2003). This note reports further observations on clutch size and hatching time of H. caesurus.